Evaluation in an Elementary Science Program. - Hill, Katherine E. (Educational Leadership, 1962)
The article reports that the moment science curriculum planning is proposed in any school, the process of evolution begins. The evaluative process cannot be relegated to an end position. It must not be made synonymous with a final examination, a review of progress. Rather, evaluation needs to be envisioned as playing the key role in an elementary science program from the inception of that program. A program purporting to further certain science skills through their use would reveal, upon evaluation, that certain facilities must be available. Time and equipment are two facilities which must be available in sufficient quantities. If it is important for children to think carefully about environmental phenomena, certain provisions must be made with regard to time. If accuracy in the use of the materials of science is held to be important, there must be opportunity to practice this skill. Children need a classroom teacher who is able to provide guidance when conditions are optimum for initial learnings. Such a teacher is an indispensable asset.